DEVELOPMENT OF CREATIVE TOURISM INNOVATION BASED ON LOCAL MUAY THAI AND COMMUNITY WISDOM - Buaphuan, Nueakwan; Phethchuai, Sakchai (Journal of MCU Nakhondhat, 2026)
This research aimed to explore the potential of local Muay Thai, community wisdom, and local resources for developing creative tourism activities and to develop creative tourism innovation based on local Muay Thai and community wisdom in Thung Bo Paen Community, Lampang Province. A mixed-methods participatory research and development approach was employed. Data were collected through in-depth interviews, observation, and focus group discussions. Twenty-five key informants were purposively selected based on their roles and experience in local Muay Thai, community wisdom, community development, or tourism. The participants included Muay Thai instructors, community leaders, local scholars, community entrepreneurs, youth representatives, and tourism stakeholders. Data were analyzed using content analysis. The findings revealed that Thung Bo Paen Community possesses strong cultural capital, local wisdom, and community resources, with Khum Wong Tawan Muay Thai Camp serving as the central hub linking Muay Thai with herbal knowledge, agriculture, healthy local food, and indigenous wisdom. Tourism innovation was developed through community participation in designing tourism activities and routes, resulting in three learning bases: Khum Wong Tawan Muay Thai Camp, Thung Bo Paen Samakkhi Temple, and Uncle Samphan's Mushroom Farm. Additional outputs included a one-day community tourism program, a community tourism map, and a trilingual QR Code tourism guide in Thai, English, and Chinese. The study demonstrates that local Muay Thai can promote tourism, generate community income, foster experiential learning between visitors and local residents, and support the sustainable preservation of local wisdom and cultural identity.